Soft Fixed Point Theorems for the Soft Comparable Contractions. (11th March 2021) - Chen, Chi-Ming; Xu, Zhi-Hao; Karapinar, Erdal
Abstract : In this article, we introduce the notions of a soft inf -comparable contraction and soft comparable Meir-Keeler contraction in a soft metric space. Furthermore, we prove two soft fixed point theorems which assure the existence of soft fixed points for these two types of comparable contractions. The obtained results not only generalize but also unify many recent fixed point results in the literature.